An investigation of customers’ intention to use self-collection services for last-mile delivery - Yuen, Kum Fai (2018)
Anchored on Innovation Diffusion Theory (IDT), this paper analyses customers' intention to use self-collection as a last-mile delivery method. Characteristics of innovation were hypothesised to be key factors influencing cus- tomers' intention to use self-collection services. Demographic characteristics were also tested. Survey data were collected from 164 consumers located in Singapore and analysed using hierarchical regression analysis. The re- sults show that among the five key characteristics of innovation, relative advantage, compatibility and trialability positively influence customers' intention to use self-collection services. It is also found that the pre-eminent step to improve customers' intention is to integrate self-collection into consumers’ lifestyle, values and needs. In addition, self-collection services should be marketed in a manner that confers a clear advantage over other last-mile de- livery methods. This paper enriches the literature on IDT as well as the management and design of self-collection services for last-mile delivery.